Indocyanine green near-infrared imaging-guided lymph node dissection during oesophageal cancer surgery: A single-centre experience - Chen, Saihua; Tian, Xiaofeng; Ju, Guanjun; Shi, Minxin; Chen, Yibiao; Wang, Qing; Dai, Wencheng; Li, Tinghua; Pan, Jing; Fan, Yihui (Frontiers in Surgery, 2023)
Objective: This study aimed to investigate the feasibility of using indocyanine green (ICG) near-infrared (NIR) imaging during lymphadenectomy for oesophageal cancer. Methods: Eighty-seven patients with primary oesophageal cancer were enrolled in this study. All the enrolled patients received an endoscopic injection of ICG between 40 min and 23 h before surgery. Nodal dissection during surgery was performed under fluorescence imaging visualisation, with the NIR signal shown in purple. ICG+ or ICG− nodes were recorded station by station and were microscopically evaluated. Results: Endoscopic peritumoral ICG injection was successfully performed in all patients. Major post-surgery complications included wound infection, pleural effusion, dysphonia, pneumonia and anastomotic fistula. No patients experienced ICG-related adverse events. A total of 2,584 lymph nodes were removed, and the mean number of lymph nodes for each patient was 29.70 ± 9.24. Most of the removed nodes (97.83%) were ICG+, and 3.32% of the ICG+ nodes were metastatic. No metastatic nodes were ICG− or belonged to an ICG− lymph node station. The time from ICG injection to surgery did not affect the number of harvested lymph nodes. Conclusions: The use of ICG-NIR imaging during oesophageal cancer surgery can enhance the visualisation of lymph nodes during surgery. It is a feasible, safe and helpful technique for lymphadenectomy.